2020
DOI: 10.3389/fphar.2020.01258
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Drugs, Ongoing Vaccine, and New Therapeutic Development Initiatives Against COVID-19

Abstract: As the COVID-19 is still growing throughout the globe, a thorough investigation into the specific immunopathology of SARS-CoV-2, its interaction with the host immune system and pathogen evasion mechanism may provide a clear picture of how the pathogen can breach the host immune defenses in elderly patients and patients with comorbid conditions. Such studies will also reveal the underlying mechanism of how children and young patients can withstand the disease better. The study of the immune defense mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 236 publications
(281 reference statements)
2
108
0
2
Order By: Relevance
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, which is widely referred to as "COVID-19", has been infecting more than 5.5 million over 144 countries. [1][2][3] The pandemic poses a significant threat to the public health system, 3,4 including catastrophic economic consequences around the world. Saudi Arabia has been plagued with several pandemics, including the Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and the ongoing COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, which is widely referred to as "COVID-19", has been infecting more than 5.5 million over 144 countries. [1][2][3] The pandemic poses a significant threat to the public health system, 3,4 including catastrophic economic consequences around the world. Saudi Arabia has been plagued with several pandemics, including the Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and the ongoing COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 As of 17th October 2020, the virus has rapidly spread in the Kingdom, causing a total of 341,495 laboratory-confirmed cases with 5144 deaths. 7 A vaccine is considered to be the most awaiting intervention 2,4,7 and hundreds of global R&D institutions engaged in unprecedented speed to develop the vaccine [7][8][9][10][11] However, public perception towards COVID-19 vaccine uptake is not available. Numerous studies have shown several factors responsible for vaccine acceptancy when a new vaccine is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…10 Humanized nano-bodies and human antibodies Attach to or intervene with the biological activity of viral proteins e.g. 3CLpro (cysteine-like protease), PLpro (papain-like protease) and Nsps (non-structural proteins) that are being replicated, hence impeding viral replication and transcription [13,35] 11 Epitope-based vaccine E protein's possible B cell epitopes and Nucleocapsid (N) protein of MERS-CoV can elicit neutralizing antibody reactions and responses of T-cell [17,18] 12 Live-attenuated vaccine Deploying reverse genetic techniques to disable the nonstructural protein 14 exonuclease consequences or remove the SARS envelope protein [19] 13 Antigen-based vaccine RBD-FP fusion protein has been developed that has shown to produce a large titer of antibodies in mice [20] 14 Live-attenuated vaccine Codon deoptimization process on virus is carried out or employed to produce a live-attenuated SARS-CoV-2 vaccine [20,21] 15 mRNA vaccine (mRNA-1273)…”
Section: Resultsmentioning
confidence: 99%
“…Codagenix Inc. has stated that it is collaborating with India's Serum Institute, Ltd. for producing live-attenuated SARS-CoV-2 vaccine [20]. Codon deoptimization process on virus is carried out or employed to produce a live-attenuated vaccine that is "rationally engineered" [20,21].…”
Section: Live-attenuated Virus Vaccinementioning
confidence: 99%
“…The bromodomains act as a reader in cell growth and a writer in cell cycle progression of histone acetylation that plays important roles in different biological processes including memory formation, replication, mitochondrial oxidative phosphorylation, transcription, DNA repair and and DNA damage response (5). Molecular structure can be determined in heterodox interpretations by solving the time-independent (11) Schrödinger equation: QM methods, (12) vertex prizes and edge costs including ab initio (13) Density Filed Theories (DFT) and semi-empirical in place of the quantum processor and (14) energy among other observables, (15) under simulated (16) error as well as (17) to reposition drugs (18) about bonding may represent the (19) similarities and dissimilarities (20) between drugs and (21) repurposed viral (22) proteins respectively. (23) However, the Schrödinger equation (24) cannot actually be solved for any (25) but a one-data-driven (26) electron system methods (the hydrogen atom), (27) and approximations (28) need to be made.…”
Section: Introductionmentioning
confidence: 99%